Self-Determination: What Does It Mean for Ethnic Minorities? Lessons for Myanmar from Aceh-Indonesia Experience. - Mangshang, Yaw Bawm. (Tufts Archival Research Center, 2015)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: (1) What are the historical narratives of both sides in regard to the conflict? (2) What gave Gerakan Aceh Merdeka (GAM) the ability to achieve what it was able to? (3) What made the Indonesian government come to a political agreement with GAM? (4) How did the international community influence the political negotiation process between GAM and the Indonesian government? (5) What specific lessons can be drawn from the principle of self-determination and the Aceh-Indonesia conflict resolution experience?